Activation of the M3AChR and Notch1/HSF1 Signaling Pathway by Choline Alleviates Angiotensin II-Induced Cardiomyocyte Apoptosis. (31st August 2021) - Xu, Man; Bi, Xue-Yuan; Xue, Xiao-Rong; Lu, Xing-Zhu; Li, Qiong-Ge; Jian, Qiang; Sun, Jian-Yong
Abstract : Angiotensin II- (Ang II-) induced cardiac hypertrophy and apoptosis are major characteristics of early-stage heart failure. Choline exerts cardioprotective effects; however, its effects on Ang II-induced cardiomyocyte apoptosis are unclear. In this study, the role and underlying mechanism of choline in regulating Ang II-induced cardiomyocyte apoptosis were investigated using a model of cardiomyocyte apoptosis, which was induced by exposing neonatal rat cardiomyocytes to Ang II (10 −6 M, 48 h). Choline promoted heat shock transcription factor 1 (HSF1) nuclear translocation and the intracellular domain of Notch1 (NICD) expression. Consequently, choline attenuated Ang II-induced increases in mitochondrial reactive oxygen species (mtROS) and promotion of proapoptotic protein release from mitochondria, including cytochrome c, Omi/high-temperature requirement protein A2, and second mitochondrial activator of caspases/direct inhibitor of apoptosis-binding protein with low P. The reversion of these events attenuated Ang II-induced increases in cardiomyocyte size and numbers of terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling-positive cells, presumably via type 3 muscarinic acetylcholine receptor (M3AChR). Indeed, downregulation of M3AChR or Notch1 blocked choline-mediated upregulation of NICD and nuclear HSF1 expression, as well as inhibited mitochondrial apoptosis pathway and cardiomyocyte apoptosis, indicating that M3AChR and Notch1/HSF1 activation confer the protective effects of choline. In vivo studies were performed in parallel, in which rats were infused with Ang II for 4 weeks to induce cardiac apoptosis. The results showed that choline alleviated cardiac remodeling and apoptosis of Ang II-infused rats in a manner related to activation of the Notch1/HSF1 pathway, consistent with the in vitro findings. Taken together, our results reveal that choline impedes oxidative damage and cardiomyocyte apoptosis by activating M3AChR and Notch1/HSF1 antioxidant signaling, and suggest a novel role for the Notch1/HSF1 signaling pathway in the modulation of cardiomyocyte apoptosis.